Risk factors for measles infection in 0–7 month old children in China after the 2010 nationwide measles campaign: A multi-site case–control study, 2012–2013. Issue 51 (12th December 2016) - Ma, Chao; Gregory, Christopher J.; Hao, Lixin; Wannemuehler, Kathleen A.; Su, Qiru; An, Zhijie; Quick, Linda; Rodewald, Lance; Ma, Fubao; Yan, Rui; Song, Lizhi; Zhang, Yanyang; et al.
Highlights: Hospital exposure was strongly associated with measles in Chinese infants. >40% of measles infections in pre-vaccine age children in China may be nosocomial. Better infection control practices are needed to further reduce measles in China. Further targeted messaging for Chinese parents on appropriate timing and contraindications for vaccines appear to be needed. Abstract: Introduction: Endemic measles persists in China, despite >95% reported coverage of two measles-containing vaccine doses and nationwide campaign that vaccinated more than 100 million children in 2010. We performed a case–control study in six Chinese provinces during January 2012 through June 2013 to identify risk factors for measles infection among children aged 0–7 months. Methods: Children with laboratory-confirmed measles were neighborhood matched with three controls. We interviewed parents of case and control infants on potential risk factors for measles. Adjusted matched odds ratios (mOR) and 95% confidence intervals (CIs) were calculated by multivariable conditional logistic modeling. We calculated attributable fractions for risk factors that could be interpreted as causal. Results: Eight hundred thirty cases and 2303 controls were enrolled. In multivariable analysis, male sex (mOR 1.6 [1.3, 2.0]), age 5–7 months (mOR 3.9 [3.0, 5.1]), migration between counties (mOR 2.3 [1.6, 3.4]), outpatient hospital visits (mOR 9.4 [6.6, 13.3]) and inpatient hospitalization (mOR 107.1 [48.8, 235.1]) were significant risk factors. The calculated attributable fractions for hospital visits was 43.1% (95% CI: 40.1, 47.5%) adjusted for age, sex and migration. Conclusions: Hospital visitation was the largest risk factor for measles infection in infants. Improved hospital infection control practices would accelerate measles elimination in China.